Imperata cylindrica sp as Novel Silica-Based Heterogeneous Catalysts for Transesterification of Palm Oil Mill Sludge - Zainab, Ngaini; Nurfarahen, Jamil; Farra Diana, Shahrom; Zainal Abiddin, Ahmad (Japan Oil Chemists Society, 2016)
Biodiesel from palm oil mill sludge (POMS) was prepared in the presence of novel silica-based heterogeneous catalysts derived from Imperata cylindrica sp. Imperatacid and Imperatabase are two types of heterogeneous catalysts derived from Imperata cylindrica sp and characterized using scanning electron microscopy, Energy Dispersive X-ray, Brunauer-Emmett-Teller surface area and pore size measurement. Imperatacid has particle size of 43.1-83.9 µm while Imperatabase in the range of 89-193 µm. Imperatacid was conveniently applied in esterification step to afford > 90 wt% oil in 1:3 (oil/methanol) and 10 wt% catalyst, followed by transesterification with 1 wt% Imperatabase and 1:1 (oil/methanol) for 1 h at 65°C to afford 80% biodiesel with higher percentage of methyl palmitate (48.97%) and methyl oleate (34.14%) compare to conventional homogeneous catalyst. Reusability of the catalyst up to three times afforded biodiesel ranging from 78-80% w/w. The biodiesel was demonstrated onto alternative diesel engine (Megatech®-Mark III) and showed proportional increased of torque (ɽ) to biodiesel loading.